(untitled) (Medico Legal Update, 2021)
Health care workers are always exposed to physical, chemical, psychological and biological agents that affect their health. Regular information is serious for setting priorities necessary to enhance providers, health and safety, which healthcare facilities like other high danger workplaces are categorized by a high level of exposure to hazards agents, which significant danger toward health of workers. A descriptive cross sectional study is carried out throughout (1/September/2019 to 1/September/2020) in order to assess the Health Workers Toward “Occupational Health and safety program” and to find out the relationships between knowledge’s of health workers toward occupational safety and health program and their socio-demographic. The study findings indicate that there is a significance relation among health worker’s knowledge about occupational health and safety program with their level of educational and their age. As well as findings show that there is a highly significance relation between knowledge about occupation health and safety program with the training of course that health workers participatedin. The study concludes that health workers Age, level education, training course, monthly income, and Number of years of Employment Have a great effect on occupational health and safety program. The study recommends Encourage health care workers to attend continuing education activities in the form of workshops, conferences, training programs, refreshing courses and review update related to “occupational health and safety program” and ministry of Iraqi health could improve the infections protective processes as “head cap, closed shoes, gloves, and frequent medical examination for communicable diseases” as hepatitis.